Trait-Factor Counselling Approach on Senior Secondary Student’s Career Choice in Kogi State, Nigeria - Agunzi, Mathew Ndako; Momoh, Grace O.; Mallum, Yakubu A. (NIU Journal of Social Sciences, 2020)
This paper examines Trait-Factor Counselling Approach on Senior Secondary Student’s Career Choice in Kogi State, Nigeria. Students are faced with the dilemma of choosing a lucrative and befitting career that they would pursue in time. This makes students prone to different opinion from parents, teachers and peer. Hence, the need for proper career counselling using the trait- factor counselling approach. The trait and factor theory operates under the premise that it is possible to measure both individual talents and the attributes required in particular jobs. Trait-factor counselling approaches assume that career choice may be facilitated and career outcomes optimized through a fairly straight forward process of matching an individual’s most relevant work-relevant characteristics (abilities, interests, values, etc) with information regarding job activities, demands, rewards, and availability. The counselling process for this approach typically starts with a client interview, then proceeds to extensive psychometric assessment of the client’s work-relevant characteristics, and is finalized with an interpretation of assessment results with connections being drawn between these results and one or more occupational classification systems. Many factors can influence or come into play in students’ career choice such as interest in field, academic ability, familiarity, economic stability, and influential people can all play a role in their career choice. Conclusions and recommendations were made. Keywords: Trait-Factor Counselling Approach, Career Choice, Career Counselling, Career Guidance and Counselling, Career Decision Making